Demand uncertainty, inventory, and cost structure - Chang, Xin; Kwok, Wing Chun; Wong, George (Contemporary Accounting Research, 2024)
Abstract Building on Banker, Byzalov, and Plehn‐Dujowich's (2014, The Accounting Review , 89 (3), 839–865) congestion cost theory, we model firms' trade‐off between a rigid cost structure and a high inventory level to reduce the congestion costs caused by uncertain demand. We demonstrate that firms with a higher inventory level adopt a less rigid cost structure, but the effect of cost structure on inventory is theoretically ambiguous. Using a large sample of manufacturing firms in the United States, we empirically investigate the dynamic interdependence between cost structure and inventory choices. Our results reveal that cost structure rigidity and inventory are negatively associated with each other over time, suggesting that they serve as substitutes in tackling demand uncertainty. Further analysis demonstrates that firms favor higher inventory levels over more rigid costs when inventory‐carrying costs decrease, fixed input costs increase, or downside risk escalates.